PENGARUH SOSIALISASI PERPAJAKAN, PENGETAHUAN PERPAJAKAN, PERSEPSI WAJIB PAJAK TENTANG SANKSI PAJAK DAN IMPLEMENTASI PP NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI ( Studi Empiris pada Wajib Pajak di Kabupaten Banjarnegara ) - Hana Pratiwi Burhan; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the factors that affect an individual taxpayer compliance in Banjarnegara. This study consists of four independent variables and the dependent variable. independent variable in this study is the socialization of taxation, tax knowledge, perceptions taxpayer about tax penalties and taxpayers perception on the implementation of PP 46 tahun2013. While the dependent variable in this study is the individual taxpayer compliance.This study used a simple random sampling technique and using the questionnaire survey method in data collection, respondents were sampled individual taxpayers who are enrolled in KP2KP Banjarnegara. Research data analysis using multiple regression analysis with SPSS 16.0.Based on the analysis that has been done, this study shows that the socialization of taxation, tax knowledge, and perceptions of the taxpayer of PP 46 in 2013 and a significant positive effect on the individual taxpayer compliance. While the taxpayer perceptions about tax penalties do not affect the compliance of individual taxpayers.